1950
DOI: 10.1063/1.1699661
|View full text |Cite
|
Sign up to set email alerts
|

The Cadmium Sulfide X-Ray Detector

Abstract: The CdS x-ray detector is compared with the photo-multiplier x-ray detector. Reduced to the same solid angle the sensitivity of the CdS x-ray detector is of the same order of magnitude as the sensitivity of the photo-multiplier x-ray detector. As the internal amplification of the primarily released electron currents in CdS is of the order 103 to 104 compared with the amplification in the multiplier tube of ½×106 the conversion process of x-ray quanta in slow electrons in CdS must be more efficient than the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1954
1954
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…As a possible semiconductor host for DMSs, CdS offers great application potential in optoelectronic devices, photocatalysts, solar cells, optical detectors, and nonlinear optical materials [2][3][4][5][6][7][8][9]. If room-temperature ferromagnetic CdS could indeed be designed, it would be a multifunctional material with coexisting and possibly coupled semiconducting, optical, and magnetic properties.…”
Section: Introductionmentioning
confidence: 98%
“…As a possible semiconductor host for DMSs, CdS offers great application potential in optoelectronic devices, photocatalysts, solar cells, optical detectors, and nonlinear optical materials [2][3][4][5][6][7][8][9]. If room-temperature ferromagnetic CdS could indeed be designed, it would be a multifunctional material with coexisting and possibly coupled semiconducting, optical, and magnetic properties.…”
Section: Introductionmentioning
confidence: 98%
“…There are numerous applications of quantum dots (QDs) of CdS and a few which are regularly eyed are their use as photocatalyst [1], non-linear optical material [2][3][4], in solar cells [5], X-ray detectors [6], photocatalytic solar energy stockings [7] and in display devices [8]. Thus over the years, it has been shown that QDs of cadmium sulphide and other II-VI semiconductors can be potential candidates for electronic and optoelectronic application such as QDs lasers and single electronic transistors [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium sulfide can be used as sensitizers in quantum dotsensitized solar cells. It also has application in nonlinear optics (Liu et al 2004), light-emitting diodes (Gopal et al 2009;Kar and Chaudhuri 2006), solar energy conversion (Weller 2003), thin film transistors (Duan et al 2003), gas detectors (Afify and Battisha 2000), optoelectronics (Hikmet et al 2003), photo catalysis (Huynh et al 2002), photovoltaic cells (Uda et al 1997), X-ray detectors (Frerichs 1950) and as a window material for hetero-junction solar cells because it has usually a high absorption coefficient (Oladeji et al 2000). Doping with transition metal elements into CdS nanoparticles leads to many interests.…”
Section: Introductionmentioning
confidence: 99%